크리핑 벤트그래스에서 동전마름병 방제를 위한 Tebuconazole, Chlorothalonil 및 합제 처리 - 김영선(Young-Sun Kim); 임혜정(Hye-Jung Lim); 함선규(Suon-Kyu Ham); 이규승(Kyu-Seung Lee); 이긍주(Geung-Joo Lee) (Weed & turfgrass science, 2018)
This study was conducted to evaluate the control efficacy of dollar spot on creeping bentgrass after applying various amounts of tebuconazole, chlorothalonil and mixture of tebuconazole and chlorothalonil (tebuconazole+chlorothalonil). In effect of three fungicides on suppression against Sclerotinia homoeocarpa, tebuconazole and tebuconazole+chlorothalonil were found to inhibit more than 98% fungus growth on medium and 70% in chlorothalonil treatment. The control efficacy of tebuconazole at different rates of 31.25, 62.5, and $125a.i.\;mg\;m^{-2}$ on creeping bentgrass showed more than 80%. Application of tebuconazole ($125.0a.i.\;mg\;m^{-2}$), tebuconazole+chlorothalonil ($125.0a.i.\;mg\;m^{-2}+135.9a.i.\;mg\;m^{-2}$) and chlorothalonil ($135.9a.i.\;mg\;m^{-2}$) were suppressed 96%, 80%, 70% for the dollar spot severity, respectively. Correlation between application amount of fungicides and control efficacy of dollar spot was significantly positive, and suggested amount of tebuconazole, tebuconazole+chlorothalonil and chlorothalonil that might suppress more than 80% of dollar spot were calculated to 29.6, 132.2+142.8, and $157.0a.i.\;mg\;m^{-2}$, respectively. 본 연구는 크리핑 벤트그래스에서 발생한 동전마름병의 효율적인 방제방법을 조사하기 위해 tebuconazole의 처리량별 동전마름병 방제율과 tebuconazole과 chlorothalonil 및 두 약제의 합제 처리 시 동전마름병 방제 효과를 평가하였다. 약제 처리 농도별 항균력 조사에서 tebuconzole과 tebuconazole+chlorothalonil 합제는 98% 이상의 S. homoeocarpa 균사 억제 효과를 나타내었고, chlorothalonil는 70% 이하의 균사 억제 효과를 나타내었다. Tebuconazole의 처리량별 동전마름병 방제 효과는 31.25, 62.5 및 $125a.i.\;mg\;m^{-2}$처리구에서 모두 80% 이상의 방제율을 나타내었다. Tebuconazole과 tebuconazole+chlorothalonil 합제 처리구는 80% 이상의 방제율을 나타내나, chlorothalonil 처리구는 약 70%의 방제율을 나타내었다. 살균제의 처리량과 동전마름병 방제 효과는 정의 상관관계를 나타내었고, 80% 이상의 방제 효과를 나타내는 tebuconazole, tebuconazole+chlorothalonil 합제 및 chlorothalonil의 처리량은 각각 29.6, 132.2+142.8, 및 $157.0a.i.\;mg\;m^{-2}$으로 판단되었다.